2013
DOI: 10.1682/jrrd.2013.05.0107
|View full text |Cite
|
Sign up to set email alerts
|

Guest Editorial: Early and innovative symptomatic care to improve quality of life of ALS patients at Cleveland VA ALS Center

Abstract: INTRODUCTIONAmyotrophic lateral sclerosis (ALS) is a neurodegenerative disease of unknown etiology. However, there is good evidence to validate the theory that military service predisposes the individual to the future development of the disease [1]. As a direct result of these data, in 2008 ALS became a presumptively compensable illness for all veterans with 90 days or more of continuously active service in the military. This decision led to an influx of ALS patients into the Department of Veterans Affairs (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…Many clinics in Europe and Asia begin NIV much earlier, as shown in a recent study examining differences in international standards of care for ALS NIV ( 22 ), but over 20% of international clinics actually begin NIV later, well after functional symptoms commence ( 23 ). Irrespective, it has long been hypothesized that starting NIV earlier than the <50 FVC %predict threshold could be associated with additional benefits ( 24 , 25 ), but there has been a lack of data to illustrate this effect in a large-scale study.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinics in Europe and Asia begin NIV much earlier, as shown in a recent study examining differences in international standards of care for ALS NIV ( 22 ), but over 20% of international clinics actually begin NIV later, well after functional symptoms commence ( 23 ). Irrespective, it has long been hypothesized that starting NIV earlier than the <50 FVC %predict threshold could be associated with additional benefits ( 24 , 25 ), but there has been a lack of data to illustrate this effect in a large-scale study.…”
Section: Introductionmentioning
confidence: 99%
“…Use of telemedicine and mobile video technologies save travel cost and hospital care, while the patient could stay at home. 35 The concepts of SOC 15,16 as comprehensibility, meaningfulness, and manageability are significant for well-being during illnesses such as ALS. Therefore, nursing staff had a professional role to play in supporting patients in end-of-life situations, which require structured, clear directions and priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Two services in the United States reported that using telemedicine had avoided outpatient visits resulting in patient travel cost savings (41,42). An…”
Section: Telemedicinementioning
confidence: 99%